Pelatihan Aplikasi Mendeley Kepada Mahasiswa Tingkat Akhir Universitas Amikom Purwokerto - Putranto, Banu Dwi; Seto, Ikhsan Dwi; Nugroho, Hery Abi; Waluyo, Retno; Setiawan, Ito (Universitas Pahlawan Tuanku Tambusai, 2024)
When writing final assignments or theses, many students still have difficulty processing existing citations, this is also experienced by students at Amikom University, Purwokerto. Mistakes in taking citations such as text that does not match the thesis guidelines, text fonts and spacing are not paid attention to even though you have used tools such as using applications for citations. When the student's report was checked by the supervisor, there was still a note of improvement. When reports are submitted to the library, the reports will also be checked again to see whether they comply with the library format. The majority of student reports are returned by the library for correction. This also applies when students make journals, there are still many errors in writing citations. The aim of the training is to reduce student errors in taking citations. The activity implementation method consists of the preparation stage, implementation stage and evaluation stage. The result of this training is a reduction in student errors in citing scientific articles, books and so on.